PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SDN 52 PAGANG PANGKEP - Andi Ririn Oktaviani; Suryadi Nur (AkMen JURNAL ILMIAH, 2014)
This research discusses the management of BOS 2012 at SDN 52 Pagang Pangkep in the use of funds, accounting and financial reporting school as a financial liability on the receipt of funds BOS. This research was conducted using quantitative descriptive analysis. Based on the results obtained, it can be seen that the use of the funds in SDN 52 Pagang Pangkep in accordance with the components that allowed financing funded by the Juknis BOS 2012. Deficiencies found in the exclusion of evidence code number on the general ledger, cash ledger, bank ledger, subsidiary ledger and tax receipts are not included and does not include the tax bill number. Advice can be given to the object researchers while maintaining the principles of transparency and accountability as well as cooperatively with parties who need the information related to BOS funds in case of BOS fund managers in schools, quickly make changes to the new reporting format in accordance Juknis BOS applicable in the current budget year. In addition, further research is expected to be more thorough and detailed financial management discusses BOS.